Peran Kepala Sekolah Dalam Meningkatkan Kualitas Pendidikan SD Negeri 25 Mattirowalie Kecamatan Tanete Riattang Barat Kabupaten Bone - Salmawati; Muhammad Faisal; Wahira (PT PUSTAKA CENDEKIA GROUP, 2025)
The problem of the principal's role in improving and advancing the quality of education is a problem that must be overcome. Solving this problem will be followed by a positive impact on the surrounding community, including at SD Negeri 25 Mattirowalie, Bone Regency, where the principal also uses the role of the principal in improving the quality of education in accordance with the conditions in the environment. This study uses a qualitative method with a descriptive approach. Data were obtained by the author by conducting observations in the field and conducting in-depth interviews with sources related to the role of the principal in improving the quality of education at SD Negeri 25 Mattirowalie, Bone Regency. The conclusions obtained in this study are first, the role of the principal in improving the quality of education at SD Negeri 25 Mattirowalie uses a participatory leadership style. Second, the quality shown by teachers is still low. Third, the relevant role of the principal used by the principal of SD Negeri 25 Mattirowalie in improving the quality of teacher education is a participatory leadership style coupled with better supervision by the principal of teacher performance. The implication of this study is that the role of the principal in improving the quality of education needs to be improved in the environment of SD Negeri 25 Mattirowalie if the role used by the principal increases, it can be ascertained that the quality of education produced will increase.